QUEER THOUGHT IN THE WRITINGS OF GUACIRA LOPES LOURO - Barros, Alexsandra Gomes; Sa-Silva, Jackson Ronie (Univ Federal Mato Grosso Sul, 2023)
The article is from a documentary and bibliographic perspective, presenting theoretical clues about the queer educational thought of Guacira Lopes Louro, in order to problematize sexual education, the school and the training of teachers and teachers. We understand that the device of normalizing pedagogy, through its heteronormative operations, produces violent, demeaning and systematic subjection to effect the erasure and subalternization of sexualities qualified as abject, peripheral or abnormal. Problem-solving education, with a queer disposition, signals possibilities for education and sex education in a Post-critical perspective of citizenship.
Keywords: Sexual education; school; training of teachers and teachers; queer disposition